2006
DOI: 10.1007/s00126-006-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

Internal vein texture and vein evolution of the epithermal Shila-Paula district, southern Peru

Abstract: The epithermal Shila-Paula Au-Ag district is characterized by numerous veins hosted in Tertiary volcanic rocks of the Western Cordillera (southern Peru). Field studies of the ore bodies reveal a systematic association of a main E-W vein with secondary N55-60°W veins-two directions that are also reflected by the orientation of fluid-inclusion planes in quartz crystals of the host rock. In areas where this pattern is not recognized, such as the Apacheta sector, vein emplacement seems to have been guided by regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…At the Martha Hill mine, there is no evidence for large scale strike-slip faulting as invoked for some other deposits (e.g., Berger et al, 2003;Chauvet et al, 2006), and in particular, not for regional north-south-trending dextral strike-slip faults required by the extensional jog models for the Martha Hill mine suggested by Wellman (1954) and Sibson (1987). The prominent north-northeast-striking East Fault (Fig.…”
Section: Faultsmentioning
confidence: 92%
See 1 more Smart Citation
“…At the Martha Hill mine, there is no evidence for large scale strike-slip faulting as invoked for some other deposits (e.g., Berger et al, 2003;Chauvet et al, 2006), and in particular, not for regional north-south-trending dextral strike-slip faults required by the extensional jog models for the Martha Hill mine suggested by Wellman (1954) and Sibson (1987). The prominent north-northeast-striking East Fault (Fig.…”
Section: Faultsmentioning
confidence: 92%
“…(5) For the bonanzagrade orebodies of the Comstock Lode in Nevada, segregation into compartments of higher and lower permeability is hypothesized to be due to extensional step-overs between dextral shear zones (Berger et al, 2003), but Hudson (2003) and Hudson et al (2009) emphasize the role of normal faulting. (6) Another deposit that has been attributed to strikeslip fault control is Shila Cordillera, Peru (Cassard et al, 2000;Chauvet et al, 2006). Normal faulting controlled mineralization at Valerdena, Mexico (Hoffman et al, 2000), Midas, Nevada (Leavitt et al, 2003) and Hishikari, Japan (Naito, 1993).…”
Section: Local Structural Control Outside New Zealandmentioning
confidence: 99%
“…Examples include the Caylloma (~18 Ma, Echavarria et al, 2006), Orcopampa (~18 Ma, Gibson et al, 1990Gibson et al, , 1995, Selene (~14 Ma, Acosta et al, 2008), Shila, Paula (~11-10 Ma, Chauvet et al, 2006), and Arcata (~5.4 Ma, Candiotti et al, 1990;Carlotto et al, 2009) deposits (Fig. 1B).…”
Section: Introductionmentioning
confidence: 93%
“…Field studies shown that most of the mineralised bodies consist of the systematic association of main E-W veins and secondary N120-135 • E veins ( Figure 7) [46]. Two main stages of ore deposition are identified [47]. Stage 1 consists of a quartz-adularia-pyrite-galena -sphalerite-chalcopyrite-electrum-Mn silicates and carbonates assemblage that fills the main E-W veins (Figure 7a,b,e).…”
Section: Vein Opening and Filling Controlled By Regional-scale Structmentioning
confidence: 99%